ANALYSIS OF THE FINANCIAL PERFORMANCE OF THE SIGI REGENCY GOVERNMENT - Graciella Jevandra Palit; Djayani Nurdin; Fatlina Zainudin; Fera (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study focuses on assessing the low level of success achieved by Sigi Regency in implementing regional autonomy, which remains far from reaching fiscal independence. It also highlights the necessary measures to develop local potential in order to enhance locally generated revenue (PAD). The analysis is conducted using seven regional financial ratios through a quantitative descriptive method, based on secondary data obtained from the 2019-2023 Regional Budget Realization Reports, as stated in local accountability regulations and data published by the Central Bureau of Statistics of Sigi Regency. The findings indicate that the fiscal independence of Sigi Regency is categorized as extremely low, reflecting a continued high dependency on central government transfer funds, mainly due to the very limited contribution of PAD. Furthermore, although the effectiveness of PAD is rated as very good, its efficiency remains poor, as it is predominantly allocated to operational expenditures. This expenditure pattern has implications for regional development and signals the need for improved fiscal management. The financial growth ratio demonstrates fluctuating trends across all sectors, suggesting the region’s inability to maintain consistent financial performance. These results underscore the urgency of conducting a comprehensive evaluation and formulating strategic actions to enhance regional autonomy. This can be achieved through optimizing the potential of PAD and implementing more accurate and efficient budgetary and expenditure management practices.